Know Better, Do Better? Parental Financial Socialization’s Indirect Association with Couple Financial Communication through Financial Self-Efficacy - Rachel M Okamoto; Ashley B LeBaron-Black; Jocelyn S Wikle; Catherine W O'Neal; Chelom E Leavitt; E Jeffrey Hill (Journal of Financial Therapy, 2025)
Communication about finances with a romantic partner is difficult for many couples. The way parents teach children to approach finances may prepare emerging adults for these difficult conversations. Family financial socialization theory suggests that parents who build their children's financial self-efficacy may be key to facilitating better communication about finances. This study used a sample of 1,950 U.S. emerging adults currently in romantic relationships to investigate the role that parental financial socialization plays in the financial communication for emerging adult couples and whether financial self-efficacy explains the association between socialization and communication. In addition to the direct association between parent financial socialization and financial communication, financial socialization was indirectly associated with couple financial communication through self-efficacy. That is, individuals whose parents effectively taught them about finances (through modeling, discussion, and experiential learning) generally had high levels of financial self-efficacy and, in turn, high-quality financial communication in their romantic relationships. Implications for clinicians include using this information to better support couples’ struggles with financial communication. Helping couples develop financial skills and knowledge can help them improve their communication as a couple.
Keywords: Financial Socialization; Self-Efficacy; Communication; Emerging Adults